2008
DOI: 10.1523/jneurosci.1968-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol-Induced Enhancement of Object Memory Consolidation Involves Hippocampal Extracellular Signal-Regulated Kinase Activation and Membrane-Bound Estrogen Receptors

Abstract: The extracellular signal-regulated kinase (ERK) pathway is critical for various forms of learning and memory, and is activated by the potent estrogen 17␤-estradiol (E 2 ). Here, we asked whether E 2 modulates memory via ERK activation and putative membrane-bound estrogen receptors (ERs). Using ovariectomized mice, we first demonstrate that intraperitoneal injection of 0.2 mg/kg E 2 significantly increases dorsal hippocampal levels of phosphorylated ERK protein 1 h after injection. Second, we show that E 2 admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

31
434
7

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(473 citation statements)
references
References 48 publications
31
434
7
Order By: Relevance
“…53,54 In vivo, we have found that infusions of E 2 directly into the dorsal hippocampus increase dorsal hippocampal p42-ERK phosphorylation within 5 min of infusion. 6,55 Further, we demonstrated that ERK activation is necessary for E 2 to enhance memory formation. 6,55,56 In this series of studies, memory was tested in ovariectomized female mice trained to recognize objects in a novel object recognition task (Fig.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 63%
See 1 more Smart Citation
“…53,54 In vivo, we have found that infusions of E 2 directly into the dorsal hippocampus increase dorsal hippocampal p42-ERK phosphorylation within 5 min of infusion. 6,55 Further, we demonstrated that ERK activation is necessary for E 2 to enhance memory formation. 6,55,56 In this series of studies, memory was tested in ovariectomized female mice trained to recognize objects in a novel object recognition task (Fig.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 63%
“…6,55 Further, we demonstrated that ERK activation is necessary for E 2 to enhance memory formation. 6,55,56 In this series of studies, memory was tested in ovariectomized female mice trained to recognize objects in a novel object recognition task (Fig. 1A) that tests the ability of an animal to recognize an object they have seen before.…”
Section: O N O T D I S T R I B U T Ementioning
confidence: 63%
“…Importantly, there is a synergistic overlap between the effects of E 2 and synaptic plasticity associated with extinction learning. For example, E 2 increases activation of mitogen-activated protein kinase (MAPK) cascades during memory consolidation (Fernandez et al 2008), and MAPK signaling is required for extinction (Hugues et al 2004). Thus, E 2 may promote extinction through stimulation of MAPK cascades.…”
Section: Discussionmentioning
confidence: 99%
“…We recently showed that activation of the extracellular signal-regulated kinase/ mitogen-activated protein kinase (ERK/MAPK) signaling cascade in the dorsal hippocampus is necessary for the potent estrogen 17β-estradiol (E 2 ) to enhance novel object recognition in young female mice (1). In this study, i.p.…”
mentioning
confidence: 90%
“…In this study, i.p. injection of E 2 immediately after object recognition training significantly enhanced long-term memory and increased p42 ERK phosphorylation in the dorsal hippocampus; both effects were blocked by inhibiting MAPK kinase (MEK), the exclusive upstream activator of ERK (1).…”
mentioning
confidence: 99%